Más allá, a la derecha - Vargas, Fred; Serrat Crespo, Manuel; Vargas, Fred. (Madrid : Ediciones Siruela, 2012)
Keeping watch under the windows of the Paris flat belonging to a politician's nephew, Louis Kehlweiler catches sight of something odd on the pavement. A small white object, surrounded by the excrement of local dogs. A piece of bone. Human bone, in fact. Naturally, when Kehlweiler takes his find to the nearest police station, he faces ridicule. But the tiny fragment obsesses him so much that he stops shadowing suspicious characters in Paris and follows the trail to the tiny Breton fishing village of Port-Nicolas.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Murder -- Investigation -- France -- Fiction; Murder -- Investigation -- Fiction; Paris (France) -- Fiction; Detective and mystery fiction; Electronic books